2022
DOI: 10.1186/s13024-022-00555-7
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk of organelles in Parkinson’s disease – MiT family transcription factors as central players in signaling pathways connecting mitochondria and lysosomes

Abstract: Living organisms constantly need to adapt to their surrounding environment and have evolved sophisticated mechanisms to deal with stress. Mitochondria and lysosomes are central organelles in the response to energy and nutrient availability within a cell and act through interconnected mechanisms. However, when such processes become overwhelmed, it can lead to pathologies. Parkinson’s disease (PD) is a common neurodegenerative disorder (NDD) characterized by proteinaceous intracellular inclusions and progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 267 publications
0
5
0
Order By: Relevance
“…Surprisingly, our ndings in Fig. 2B demonstrated signi cant changes in the mTOR pathway upon exposure to excessive MMA, potentially contributing to unraveling the molecular mechanisms underlying methylmalonic acidemia, particularly in relation to the mTOR pathway, Ca 2+ , and mitophagy [41] . However, it's important to note that our study's limitation lies in focusing solely on transcriptomic analysis and the validation of the mechanism behind MMA-induced liver injury, lacking a deeper exploration of the regulatory interplay among mitophagy, ER-phagy, and Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 74%
“…Surprisingly, our ndings in Fig. 2B demonstrated signi cant changes in the mTOR pathway upon exposure to excessive MMA, potentially contributing to unraveling the molecular mechanisms underlying methylmalonic acidemia, particularly in relation to the mTOR pathway, Ca 2+ , and mitophagy [41] . However, it's important to note that our study's limitation lies in focusing solely on transcriptomic analysis and the validation of the mechanism behind MMA-induced liver injury, lacking a deeper exploration of the regulatory interplay among mitophagy, ER-phagy, and Ca 2+ homeostasis.…”
Section: Discussionmentioning
confidence: 74%
“…Interestingly, we found that most of the DEPs enriched in the “Parkinson's disease” pathway were involved in “mitochondrial dysfunction.” We reviewed the patients' history and found that none of the patients with CRSwNP had Parkinson disease. Mitochondrial dysfunction is thought to play an important role in the pathogenesis of Parkinson disease 5 . Therefore, the proteins related to mitochondrial dysfunction are enriched in “Parkinson's disease” signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial dysfunction is thought to play an important role in the pathogenesis of Parkinson disease. 5 Therefore, the proteins related to mitochondrial dysfunction are enriched in "Parkinson's disease" signaling pathways. We selected 19 proteins for PRM validation, and found that the levels of 17 proteins were consistent with the results from proteomic data, which confirmed the reliability of our omics results (Figure S4).…”
Section: Protein-metabolite Interaction Network Analysis Of Deps and ...mentioning
confidence: 99%
“…PD is associated with the dysregulation of the mitochondrial quality control system within DA neurons in the substantia nigra. Homeostasis of healthy mitochondria is achieved by fine regulation of molecules involved in mitochondrial biogenesis, mitophagy, and mitochondrial dynamics [ 44 ]. This study shows that 6-OHDA-induced damage and apoptosis of SH-SY5Y cells can be improved by enhancing mitochondrial biogenesis via CSS treatment.…”
Section: Discussionmentioning
confidence: 99%